Sejarah Muhammadiyah: Dari Awal Pendiriannya Hingga Perannya dalam Reformasi Sosial - Yupi Yani Telaumbanua; Rena Elpiana; Cindy Sri Wahyuni; Riska Aryanti; Wismanto Wismanto; Wira Ramashar (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Muhammadiyah is one of the largest Islamic organizations in Indonesia which was founded by K.H.Ahmad Dahlan in 1912 in Yogyakarta. This organization plays an important role in the renewal of religious thought and practice as well as in various aspects of social life in Indonesia. The history of Muhammadiyah covers a long journey from its founding to its role in social reform in Indonesia, making it an important subject to study. The aim of this research is to examine the history of Muhammadiyah from its initial founding to its contribution to social reform in Indonesia. By understanding the history and role of Muhammadiyah, it is hoped that it can provide deeper insight into the contribution of this organization to social reform and change in Indonesia. Method This research uses historical methods with a qualitative approach. Data was obtained through literature studies which included books, journals, articles and documents related to Muhammadiyah. The research results show that since its inception, Muhammadiyah has focused on education and health reform, which then developed into a broader social reform movement. Apart from that, Muhammadiyah also plays an important role in advocating social and political issues related to justice and equality. Muhammadiyah's role in social reform includes various initiatives in education, health, and social welfare that continue to this day. Conclusion Muhammadiyah has shown a significant role in Indonesian history, not only as a religious organization but also as an agent of social change. Muhammadiyah's contribution to social reform has had a broad positive impact on Indonesian society, making it one of the important pillars in the history of social reform in Indonesia.